The comparison of Ottawa Ankle Rules and Shetty test performances in foot-ankle trauma patients visited to the emergency department - Ak, Rohat; Kurt, Erdem; Bahadırlı, Suphi; Çakır, Mehmet Semih; Bilgu, Ali Selman; Eke Kurt, Şebnem Zeynep (Elsevier Science Ltd, 2022)
Background: The Ottawa Ankle Rules (OARs) and Shetty test (ST), are assessment guidelines intended to minimize radiographs in patients with ankle trauma. The aim of this study is to determine and compare the effectiveness of OARs and ST in patients admitted to the emergency department (ED) with foot and ankle trauma. Methods: This prospective cohort study was carried out in the ED of a tertiary care teaching hospital. OARs and ST were practiced by different doctors to patients, who were admitted with foot and ankle trauma. X-ray images were analyzed by a radiologist. Accuracy measures were covered such as sensitivity, specificity, positive predictive value, negative predictive value. Results: The study was completed a total of 207 patients, after achieving the inclusion and exclusion criteria. The mean age of the patients was 33.1 +/- 16.3, and 96 (46.4%) were female. For OARs, it was determined that as sensitivity 97.22%, specificity 48.89%, positive predictive value 50.36%, negative predictive value 97.06%, positive likelihood ratio 1.9 and negative likelihood ratio 0.06. If the OARs had been used, there would have been a 32.8% reduction in the ankle X-ray system. For the ST, it was determined that as sensitivity 51.39%, specificity 85.93%, positive predictive value 66.07%, negative predictive value 76.82%, positive likelihood ratio 3.65 and negative likelihood ratio 0.57. Discussion: The OARs can be used as a screening tool, due to causing the high sensitivity in foot and ankle traumas. The ST was found to be inefficient in this study. In addition, the significant reduction in the number of X-rays with the use of OARs is another major result of the study.
Keywords: Ankle; Foot; Fracture; Ottawa; Shetty; Trauma